Stabilization and Preservation of Bioactive Compounds in Black Elderberry By-Product Extracts Using Maltodextrin and Gum Arabic via Spray Drying - Zorana Mutavski; Senka Vidović; Zorica Lazarević; Rita Ambrus; Anett Motzwickler-Németh; Krunoslav Aladić; Nataša Nastić (Foods)
This study investigates the encapsulation efficiency and physicochemical properties of black elderberry pomace powders obtained by a spray-drying process employing maltodextrin and gum arabic as encapsulating agents. The formulations SD 1 to SD 6 were prepared in different ratios, from 100% maltodextrin (SD 1) to 100% gum arabic (SD 6). The encapsulation yield (EY) ranged from 75.36% to 83.84%, with SD 1 achieving the highest EY of 83.84%. Particle size analysis revealed average sizes between 1.73 μm and 2.20 μm, with SD 2 showing a uniform distribution. Flow and compressibility studies showed that SD 4 (40% maltodextrin, 60% gum arabic) had better flow properties (Carr index of 27.34) compared to SD 1 (Carr index of 39.91). The retention of bioactive compounds showed that SD 1 retained cyanidin 3-O-sambubioside at 17.55 mg/g and cyanidin 3-O-glucoside at 14.20 mg/g, while SD 4 showed high efficiency for kaempferol derivate 1 (97.86% in SD 5) and kaempferol derivate 2 (98.57% in SD 4). Overall, SD 4 proved to be the optimal formulation, significantly enhancing the stability and bioavailability of elderberry extract in food and nutraceutical applications. This is attributed to its high encapsulation efficiency and effective retention of bioactive compounds, making it an ideal candidate for incorporation into functional foods and dietary supplements aimed at promoting health benefits.